Change in Experiential Avoidance is Associated with Reduced Suicidal Ideation over the Course of Psychiatric Hospitalization. Issue 3 (2nd July 2016) - Ellis, Thomas E.; Rufino, Katrina A.
Abstract : Growing empirical literature in recent years indicates that experiential avoidance plays a role in a wide variety of psychological disorders and psychotherapeutic interventions. This study explored the view of suicidal ideation as a form of experiential avoidance by examining the association between suicidal ideation and therapeutic change in a sample of 189 adult psychiatric inpatients. Results were consistent with predictions, showing a statistically significant association between scores on the Beck Scale for Suicidal Ideation and the Acceptance and Action Questionnaire-II (AAQ-II). It was further shown that change in AAQ-II scores over the course of hospitalization was associated with change in suicidality, independent of changes in depression severity and hopelessness. Moreover, treatment responders (patients whose suicidal ideation scores dropped significantly over the course of treatment) showed greater drops in experiential avoidance relative to nonresponders. These results are consistent with a view of suicidal ideation (and, by extension, suicide) as a form of experiential avoidance and potentially a therapeutic approach that specifically seeks to reduce experiential avoidance.